Enhanced insulating and piezoelectric properties of BiFeO3‐BaTiO3‐Bi0.5Na0.5TiO3 ceramics with high Curie temperature - Cheng, Shuai; Zhang, Bo‐Ping; Zhao, Lei; Wang, Kai‐Kun (Journal of the American Ceramic Society, 2019)
BiFeO3‐BaTiO3 ceramics are promising lead‐free piezoelectric ceramics due to their high piezoelectric properties and high Curie temperature, but their high leakage current density makes the poling difficult. In this study, a decreased leakage current density by three orders of magnitude was obtained in Bi0.5Na0.5TiO3 (BNT) added 0.67BiFeO3‐0.33BaTiO3 (BF‐BT) ceramics. It was found that the largely improved insulating properties benefit from the reduced oxygen vacancies and weak reduction of Fe3+ to Fe2+ as confirmed by photoluminescence and X‐ray photoelectron spectroscopy measurements, thereby contributing to high‐temperature and high‐field poling. In addition, the introduction of BNT leaded to increased grain size. Due to the grown grains as well as reduced oxygen vacancies and Fe2+, enhanced insulating and optimal piezoelectric properties with Pr = 24.2 µC/cm2, d33 = 183 pC/N, kp = 0.28, and TC = 467°C were achieved in BF‐BT‐0.05BNT ceramics.